Inexpensive production of near‐native engineered stromas. (26th May 2015) - Chabaud, Stéphane; Rousseau, Alexandre; Marcoux, Thomas‐Louis; Bolduc, Stéphane
Abstract: Although the self‐assembly approach is an efficient method for the production of engineered physiological and pathological tissues, avoiding the use of exogenous materials, it nevertheless remains expensive and requires dexterity, which are features incompatible with large‐scale production. We propose a modification to this technique to make easier the production of mesenchymal compartment, to reduce the cost and to improve the histological quality of the self‐assembled tissues. The stroma produced by this novel approach allowed epithelial cell differentiation, resulting in a pseudostratified epithelium that shared several features with native tissues. The incorporation of endothelial cells in the reconstructed mesenchyme formed a three‐dimensional capillary‐like network, positive for CD31 and von Willebrand factor and surrounded by NG2 positive cells. It could limit self‐contraction of the resulting tissue by recruiting α ‐Smooth Muscle Actin positive cells. With this new technique, which is relatively inexpensive and easy to use in a research laboratory set‐up, near‐native stromas can now be produced with minimal handling time. Copyright © 2015 John Wiley & Sons, Ltd.